Insurgent Citizenship and Sustained Resistance of a Local Taxi Association - Matebesi, Sethulego Z. (Qualitative Sociology Review, 2019)
A growing body of literature on urban and grassroots social movements is replete with case studies of citizens mobilizing against infrastructural development projects. These mobilizations, known as insurgent citizenship—the participation in alternative channels of political expression—take different forms and have various impacts. An investigation into the case of the mobilizing agenda of the Greater Bloemfontein Taxi Association (GBTA) against using a costly intermodal transport facility in Bloemfontein is aimed at highlighting the often neglected dilemma of how powerless citizens—for example, taxi owners—respond to state hegemony. Theoretically, the article is grounded in the conceptual framework of insurgent citizenship and, empirically, draws on narratives of a range of participants. The findings provide an understanding of the importance of organizational structure and leadership in the sustained insurgent action by the GBTA. It is argued that the insurgent action by the GBTA is produced mainly by—on the one hand—the conflictual relationship between government policies and practices and—on the other hand—grassroots resistance to their exclusionary and marginalizing effects. Furthermore, the findings elucidate that insurgent practice may be driven by neoliberal principles of competition, profit, and entrepreneurship.